Blood exosome connexins and small RNAs related to demyelinating disease activity - Guzailiayi Maimaitijiang; Jun‐ichi Kira; Yuri Nakamura; Mitsuru Watanabe; Ezgi Ozdemir Takase; Satoshi Nagata; Ayako Sakoda; Xu Zhang; Katsuhisa Masaki; Ryo Yamasaki; Noriko Isobe; Hiroo Yamaguchi; et al. (Annals of Clinical and Translational Neurology)
Abstract Objectives To assess blood exosome (Ex)‐connexin (Cx)43 (encoded by GJA1) and its truncated isoforms in multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD), which show distinct alterations in astroglial Cx43. Methods Serum Exs from 48 patients with MS (34 relapsing–remitting, 14 secondary‐progressive), 35 with NMOSD, 20 with other inflammatory neurologic diseases (OIND), and 17 healthy controls (HC) were subjected to quantitative Western blotting for Cx43, single‐molecule array for neurofilament‐L, and quantitative polymerase chain reaction for non‐coding RNAs detected by RNA sequencing. Sera from control and astroglia‐specific Cx43 inducible conditional knockout (Cx43‐icKO) mice with experimental autoimmune encephalomyelitis (EAE) were also tested. Results Ex‐GJA1‐29k was markedly higher in MS than in NMOSD, OIND, and HC; it successively increased at relapse, remission, and secondary progression, and positively correlated with disability scores. Ex‐hsa‐miR‐133b and other hsa‐miRs that bind to full‐length Cx43 were significantly lower in secondary‐progressive MS than in HC, and Ex‐hsa‐miR‐133b was negatively correlated with disability scores. Ex‐GJA1‐11k expression was lower in NMOSD at relapse than in HC and OIND, and was negatively correlated with disability score worsening and Ex‐neurofilament‐L levels. NMOSD at relapse had significantly higher expression of small nucleolar RNA (SNORD37, SNORD95, and SNORD97) than HC, and SNORD37 and SNORD95 showed strong negative correlations with disability scores. Control mice showed increased Ex‐GJA1‐43k and ‐29k during EAE; this effect was markedly reduced in Cx43‐icKO mice with attenuated EAE. Interpretation Blood Ex‐Cx43‐truncated isoforms and small non‐coding RNAs, which partially come from brain astroglia, are distinctly dysregulated in MS and NMSOD.